Cladistic analysis of Thoreyella and related genera (Hemiptera: Pentatomidae: Pentatominae: Procleticini) - Bernardes, Jorge L. C.; Schwertner, Cristiano F.; Grazia, Jocélia (Zootaxa, 2009)
In this paper, the monophyly of the genus Thoreyella Spinola was tested, and a hypothesis of relationships among its species is proposed. Four known species of Thoreyella and two new species, as well as species of three other genera of Procleticini (Neoderoploa Pennington, Lobepomis Berg, and Procleticus Berg), were treated as the ingroup. The new species of Thoreyella will be published elsewhere. Two species of Dendrocoris were used for outgroup comparison. A cladistic analysis of 38 morphological characters supported a hypothesis of common ancestry for Thoreyella and the three genera of Procleticini included in the ingroup. The results also showed Thoreyella as a monophyletic taxon, and its sister group relationship with the monophyletic group including Neoderoploa, Lobepomis, and Procleticus. The geographical distribution of these taxa is discussed.